2012
DOI: 10.1111/j.2042-3292.2012.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of aquatic therapy and its potential use in managing equine osteoarthritis

Abstract: SummaryAquatic therapy has become increasingly popular in its use for rehabilitation of equine musculoskeletal injuries. Unfortunately, there has been no scientific evaluation of its clinical application for the treatment of osteoarthritis (OA) or associated musculoskeletal injuries in horses. The purpose of this review is to describe mechanisms of action of aquatic therapy and its potential use in the clinical management of equine OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
0
24
0
2
Order By: Relevance
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…In people, aquatic therapies have been reported to decrease pain 67 ; it is shown that exercising in water has beneficial effects through the following mechanisms 68 :…”
Section: Hydrotherapymentioning
confidence: 99%
“…In recent years water treadmill exercise has increased in popularity within the training and rehabilitation of sport horses. It may be incorporated into an exercise programme with the aim of minimising concussion of distal limb joints , providing controlled, straight line exercise without the weight of a rider, promoting flexion of distal limb joints or simply adding variety to the horse's work. Currently, the rationale for the use of water treadmills and exercise protocols employed vary according to the individual experiences of therapists and clinicians based on their own case results.…”
Section: Introductionmentioning
confidence: 99%